MOSkin dosimetry for an ultra-high dose-rate, very high-energy electron irradiation environment at PEER - Cayley, James; Tan, Yaw-Ren E.; Petasecca, Marco; Cutajar, Dean; Breslin, Thomas; Rosenfeld, Anatoly; Lerch, Michael (Frontiers in physics, 2024)
FLASH radiotherapy, which refers to the delivery of radiation at ultra-high dose-rates (UHDRs), has been demonstrated with various forms of radiation and is the subject of intense research and development recently, including the use of very high-energy electrons (VHEEs) to treat deep-seated tumors. Delivering FLASH radiotherapy in a clinical setting is expected to place high demands on real-time quality assurance and dosimetry systems. Furthermore, very high-energy electron research currently requires the transformation of existing non-medical accelerators into radiotherapy research environments. Accurate dosimetry is crucial for any such transformation. In this article, we assess the response of the MOS kin , developed by the Center for Medical Radiation Physics, which is designed for on-patient, real-time skin dose measurements during radiotherapy, and whether it exhibits dose-rate independence when exposed to 100 MeV electron beams at the Pulsed Energetic Electrons for Research (PEER) end-station. PEER utilizes the electron beam from a 100 MeV linear accelerator when it is not used as the injector for the ANSTO Australian Synchrotron. With the estimated pulse dose-rates ranging from ( 7.84 ± 0.21 ) × 1 0 5 Gy/s to ( 1.28 ± 0.03 ) × 1 0 7 Gy/s and an estimated peak bunch dose-rate of ( 2.55 ± 0.06 ) × 1 0 8 Gy/s, MOS kin measurements were verified against a scintillating screen to confirm that the MOS kin responds proportionally to the charge delivered and, therefore, exhibits dose-rate independence in this irradiation environment.